PENGARUH CITRA MEREK, PERSEPSI HARGA, DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PENGGUNA SMARTPHONE ANDROID SAMSUNG DI SEMARANG - Maulida Wati, 15.05.51.0376; Rizal, Alimuddin (Students' Journal of Economic and Management, 2018)
This study aims to analyze the influence of each variable of Brand Image, Price Perception, And Product Quality To Customer Satisfaction And Its Impact On Android Smartphone User Loyalty In Semarang. The population in this study is the consumers of all citizens in Semarang. The sample is determined by using purposive sampling with criteria: aged over 17 years and have used Samsung brand android smartphone. Data analysis method used is through multiple linear regression analysis, instrument test, model test and hypothesis test. The test instrument is tested with validity test and reliability test. Test model used is Test F (Goodness of Fit) and test Adj R2 (coefficient of determination). Furthermore, the hypothesis test in this study using regression analysis with t test with standard beta coefficient and significance level <0.05.Based on the results of hypothesis test concluded: 1. Brand Image have positive and significant impact on customer satisfaction. 2. Price Perceptions has a positive and significant impact on customer satisfaction. 3. Product Quality has positive and significant impact on customer satisfaction. 4. Customer Satisfaction has positive and significant impact on purchasing decision. 5. Customer Satisfaction has a positive and significant impact on Samsung android smartphone user loyalty. Keywords: price perception, service quality, location, store image, purchase decision, buying interest